Field decomposition of leaf litters: earthworm–microorganism interactions—the ploughing-in effect (Soil Biology and Biochemistry, 1998)
We describe a new decomposition model including the consequences of earthworm mechan- ical activity, especially the ploughing-in eect. In an experiment we tested this ploughing-in eect on the disappearance of leaf litter from four tree species (sessile oak, Quercus petraea L., holm oak, Quer- cus ilex L., sweet chestnut, Castanea sativa Mill and beech, Fagus sylvatica L.) during two 2 y exposure at the site of Anduze which contained the highest earthworm biomass. Our experiment, carried out with leaf litter placed in litterbags allowing (0.5 cm mesh size) or preventing (0.1 cm mesh size) the access of earthworms, con®rms (1) the rates of litter decomposition observed in the ®rst experiment and (2) the important eect of earthworms on litter decomposition (from 20.5% to 30.2% depending on the litter). The breakdown of the dierent litters by soil fauna varied from 24.2% to 40.6% depending on the litters after 2 y exposure in the ®eld at Anduze and the litter decomposition rate was increased by a mean factor of about 5.2. We describe a technique for detecting litter contamination attributed to earthworm casts. This technique is based on the change of the litter total weight loss (TWL)-to-litter total C loss (TCL) ratios which varied from 0.652 to 0.915 in the presence of earthworms and were close to 1 (from 0.952 to 0.995) in the absence of earthworms. We assumed that this large change in these ratios indicated a mineral contamination of litters due to earthworm casting. This hypothesis was con®rmed by the litter ash contents varying from 2.6% to 9.6% with earthworms and from 1.3% to 2.1% without earthworms only. These results point out the ecological importance of contamination of the litter by casts during decomposition.

Decomposition of mediterranean leaf litters: A microcosm experiment investigating relationships between decomposition rates and litter quality (Soil Biology and Biochemistry, 1996)
he decomposition of four mediterranean species leaf litter (Sessile oak, Quercus petraea L.; Holm oak, Quercus ibex L.; Sweet chestnut, Castanea satiua Mill and beech, Fagus syluatica L.) was studied for 90 days under controlled conditions. Respiration and litter mass loss were measured in three types of microcosms: (1) Soil only; (2) Soil + l-y old litter and (3) Soil + l-y old litter + newly senescent litter (freshly fallen). Variations in chemical composition of the litters were determined before and after incubation by the pyroanalysis method. For newly senescent litters decomposition rates per day Kco, (calculated from CO, release) and K, (calculated from mass losses) fitted to the first order exponential decay decreased as follows: sessile oak (Kc,_,, = 0.0043; K, = 0.0049) > holm oak (Km, = 0.0031; K, = 0.0040) = beech (&o~ = 0.0030; K, = 0.0030) > sweet chestnut (Kc% = 0.0001; K,, = non- significant regression); For l-y old litters sweet chestnut (Ko,, = O.oo40, K, = 0.0065) > sessile oak (KEO, = 0.0035; K, = 0.0039) > beech (Kcc,, = 0.0030; K, = non-significant regression). All litters showed a reduction of lipid (mean loss 90.5%), hydrosoluble (mean loss, 54.2%), hemicellulose plus cellulose (mean loss, 40.6%) content and a relative increase of lignin content (mean gain, 34.4%). Among indicators of litter quality (C-to-N ratio, %N, %lignin, lignin-to-N ratio, HLQ), only some of them were correlated with litter decay. The best relationships were established between the decomposition rates (K,) and parameters integrating lignin contents (I = 0.997; n = 3; P < 0.01). The decomposition of l-y old litters fitted well with most of these parameters (0.999 < I < 0.997; n = 3; P < 0.01) in contrast to newly senescent litters